2017
DOI: 10.1038/srep41421
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a divergent progenitor cell sub-populations in human osteoarthritic cartilage: the role of telomere erosion and replicative senescence

Abstract: In recent years it has become increasingly clear that articular cartilage harbours a viable pool of progenitor cells and interest has focussed on their role during development and disease. Analysis of progenitor numbers using fluorescence-activated sorting techniques has resulted in wide-ranging estimates, which may be the result of context-dependent expression of cell surface markers. We have used a colony-forming assay to reliably determine chondroprogenitor numbers in normal and osteoarthritic cartilage whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 39 publications
(60 reference statements)
4
90
0
Order By: Relevance
“…A few prior studies used manual counting methods to measure P CTP‐C and [CTP‐C]. In these reports, P CTP‐C was between 0.1% and 0.2%, or 1,000 and 2,000 progenitors/million cells plated, consistent with our mean of 1,300 CTP‐Cs per million cells. Based on stem cell marker expression, Grogan et al have demonstrated that in comparison to normal cartilage, progenitor cells decrease in non‐fibrillated OA superficial zone and increase in fibrillated OA superficial zone.…”
Section: Discussionsupporting
confidence: 86%
“…A few prior studies used manual counting methods to measure P CTP‐C and [CTP‐C]. In these reports, P CTP‐C was between 0.1% and 0.2%, or 1,000 and 2,000 progenitors/million cells plated, consistent with our mean of 1,300 CTP‐Cs per million cells. Based on stem cell marker expression, Grogan et al have demonstrated that in comparison to normal cartilage, progenitor cells decrease in non‐fibrillated OA superficial zone and increase in fibrillated OA superficial zone.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies reported that CPC frequency and proliferation increase in pathological cartilage [34,35], but they are not influenced by donor age [34,36].…”
Section: Pl Induced Release Of Cells With Fibroblastic-like Phenotypementioning
confidence: 79%
“…1). 15,17 These cells have been established as not only clonable but also able to differentiate into chondrocytes with the stable cartilage phenotype, [14][15][16][17][18][19][20] which makes them a potentially superior cell type to use for therapies such as those suggested by Brunger et al 11 However, we have also found clones that will consistently undergo endochondral chondrogenesis. 14 In a recent study, we tested human ACP clones from multiple biological replicates for their chondrogenicity in pellet culture at physioxia (defined as 2-5% oxygen for human articular cartilage) and hyperoxia (20% oxygen).…”
Section: Cellular Basis Of Chondrogenesis For Cartilage Repairmentioning
confidence: 74%
“…In a recent study, we tested human ACP clones from multiple biological replicates for their chondrogenicity in pellet culture at physioxia (defined as 2–5% oxygen for human articular cartilage) and hyperoxia (20% oxygen) . As reported by Archer's group, the majority of clones appeared to make cartilage of a stable phenotype, expressing hypertrophic markers (COLXA1, MMP13) only at or below the level of detection. Physioxia decreased any detectable hypertrophic markers even further .…”
Section: Cellular Basis Of Chondrogenesis For Cartilage Repairmentioning
confidence: 93%
See 1 more Smart Citation